Evaluation of the fetal heart rhythm in clinical practice – review - Nowakowska, Aleksandra; Sylwestrzak, Oskar; Respondek-Liberska, Maria; Murlewska, Julia (Prenatal Cardiology, 2021)
Fetal heart rate (FHR) monitoring is one of the most important methods during the prenatal period to assess fetal wellbeing. An exact structural depiction of the cardiac anatomy and physiology are essential for the definitive prenatal diagnosis of normal heart anatomy and normal heart rhythm or cardiac defect or abnormalities in fetal heart rhythm. This is a literature review about the different modalities currently available for FHR assessment. Basic ultrasound examination includes an assessment of placenta, amniotic fluid index, fetal position, its biometry, and peripheral Doppler blood flows, i.e. umbilical artery and umbilical vein, and the middle cerebral artery. The next step is usually fetal anatomy evaluation: brain, neck, chest, abdomen, skeletal, and fetal heart. Fetal heart evaluation can be basic to confirm normal heart anatomy, normal intracardiac blood flows, normal heart rate, and normal heart rhythm. In case of detection of any abnormality a targeted fetal echocardiography assessment is recommended. Fetal echocardiography is considered a highly sensitive specific prenatal tool not only for detection but also diagnosis of congenital heart disease. Fetal echocardiography facilitates the prenatal diagnosis and through sequential examinations, and allows longitudinal assessment of fetal haemodynamics and cardiovascular status from the time of diagnosis to delivery. In this review we describe different methods of fetal heart rhythm assessment in the context of clinical fetal cardiology, and compare their advantages and disadvantages. This manuscript may be a didactic introduction to fetal echocardiography for beginners, before the next step: an attempt at recording and analysing fetal heart arrhythmias.